Outcome of severe infections in afebrile neutropenic cancer patients - Strojnik, Ksenija (Radiology and oncology (Ljubljana), 2016)
In some neutropenic cancer patients fever may be absent despite microbiologically and/or clinically confirmed infection. We hypothesized that afebrile neutropenic cancer patients with severe infections have worse outcome as compared to cancer patients with febrile neutropenia. Patients and methods. We retrospectively analyzed all adult cancer patients with chemotherapy-induced neutropenia and severe infection, who were admitted to the Intensive Care Unit at our cancer center between 2000 and 2011. The outcome of interest was 30-day in-hospital mortality rate. Association between the febrile status and in-hospital mortality rate was evaluated by the Fishers exact test. Results. We identified 69 episodes of severe neutropenic infections in 65 cancer patients. Among these, 9 (13%) episodes were afebrile. Patients with afebrile neutropenic infection presented with hypotension, severe fatigue with inappetence, shaking chills, altered mental state or cough and all of them eventually deteriorated to severe sepsis or septic shock. Overall 30-day in-hospital mortality rate was 55.1%. Patients with afebrile neutropenic infection had% a trend for a higher 30-day in-hospital mortality rate as compared to patients with febrile neutropenic infection (78% vs. 52%, p = 0.17).
Keywords: afebrile infection; afebrilna infekcija; cancer patients; hipotermija; hypothemia; neutropenia; nevtropenija; onkološki bolniki